The Influence of Leadership Style and Workload on Employee Work Stress at the Civil Service Police Unit Office (SATPOL PP) South Sulawesi Province - Safitri (Pustaka Digital Indonesia, 2024)
This research is a type of quantitative research with the aim of finding out the influence of leadership style and workload on employee work stress at the South Sulawesi Province Civil Service Police Unit (Satpol pp) office. This sample was taken from the South Sulawesi Province Civil Service Police Unit (Satpol pp) office. The type of data used in this research is quantitative data obtained from distributed questionnaires and is related to the problem being studied. Data collection was carried out by observation and distribution of questionnaires. In this research, the data sources used in data collection include primary data and secondary data. The research instrument used in this research used the Likert scale method. Based on the results of data research using statistical calculations through the Statistical Package for the Social Science (SPSS) version 24 application regarding the influence of leadership style and workload on employee work stress at the South Sulawesi Province Civil Service Police Unit (Satpol PP) office as discussed in the previous chapter, So the author draws an important conclusion, namely that leadership style has a positive and significant effect on employee work stress at the Civil Service Police Unit Office (Satpol PP) South Sulawesi Province, while workload has a significant effect on employee work stress at the Civil Service Police Unit Office (Satpol PP) Sulawesi Province South.